Exploring the relationship between mental health professionals and family caregivers, who care for 18-30 year olds, diagnosed with a serious mental illness, in two district healthe board areas of NZ : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Rehabilitation at Massey University - Nicholls, Elizabeth A (Massey University, 2004)
Despite compelling evidence of benefits for mentally ill family members when there is a working relationship between mental health professionals (MHPs) and family caregivers (FCGs), international and New Zealand literature has continued to reveal that the relationship is fraught with difficulties. Although there have been a number of international studies exploring the relationship from the family caregiver perspective there have been few international studies and no New Zealand studies conducted that have explored the MHPs perspective of this relationship. Therefore the purpose of this research was to explore this relationship from the FCG's perspective and the MHP's perspective. In-depth interviews were conducted with six FCGs and seven MHPs, one of whom was also a FCG, from two North Island District Health Board areas. Four MHP themes and five FCG themes were identified which highlight a significant chasm that exists between the MHP's intention to build a relationship with the FCG, and the FCG's experience of the nature of this relationship. These findings are discussed and recommendations are made to bridge this chasm for the benefit of FCGs and MHPs, but ultimately the person with the mental illness.
Keywords: New Zealand; Mental health personnel; Community mental health services; Families of the mentally ill; Mental illness; Caregivers